2008
DOI: 10.1007/s00442-008-1113-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil temperature, digging behaviour, and the adaptive value of nest depth in South American species of Acromyrmex leaf-cutting ants

Abstract: In leaf-cutting ants, workers are expected to excavate the nest at a soil depth that provides suitable temperatures, since the symbiotic fungus cultivated inside nest chambers is highly dependent on temperature for proper growth. We hypothesize that the different nesting habits observed in Acromyrmex leaf-cutting ants in the South American continent, i.e. superficial and subterranean nests, depend on the occurrence, across the soil profile, of the temperature range preferred by workers for digging. To test thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
1
5

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 42 publications
3
98
1
5
Order By: Relevance
“…For Acromyrmex, climatic conditions can explain aspects of the mentioned differences regarding the presence/absence of a mound [18] and dump location either interspecifically (Farji Brener, pers. com.)…”
Section: Leaf-cutter Antsmentioning
confidence: 99%
“…For Acromyrmex, climatic conditions can explain aspects of the mentioned differences regarding the presence/absence of a mound [18] and dump location either interspecifically (Farji Brener, pers. com.)…”
Section: Leaf-cutter Antsmentioning
confidence: 99%
“…Growth rates of tropical Attamyces fungi are optimized around 25°C; growth stagnates below 20°C, and prolonged exposure to temperatures below 10°C can be lethal to tropical Attamyces (12)(13)(14). Tropical leafcutter ants therefore construct fungal chambers that maintain gardens within a temperature window of 20 to 30°C, typical temperatures for tropical rainforest soils (15)(16)(17)(18)(19). Moreover, leafcutter ants possess an antennal sensitivity to temperature gradients that is far more acute than in any other insect (20), and this sensitivity enables leafcutter workers to rapidly assess temperature gradients.…”
mentioning
confidence: 99%
“…Leafcutter ants can protect their gardens against some environmental fluctuations (18,19), but the northernmost A. texana populations experience harsh winters in which soils can freeze for prolonged times to significant depths (Table S1). A. texana ants can prevent garden desiccation by foraging for groundwater in their nests' deep tunnel systems [reaching as deep as 32 m (27)] and by supplying gardens with moisture during fungiculture [e.g., manuring of gardens with droplets of liquid feces (11,28,29)].…”
mentioning
confidence: 99%
“…In this perspective, we can hypothesize that nest exposed in grassland should have deeper fungus chamber than nest under shade of trees or inside the woods, given that soil temperature is negatively correlated with soil depth (Rosenberg et al, 1983). For leaf cutting ants, is indicated that soil moisture and temperature acts together: (i) Bollazzi et al (2008) verified that workers' thermopreferences lead to the construction of superficial nests in cold soils, and subterranean ones in hot soils; and (ii) Pielström & Roces (2014) verified that soil moisture also varies according to soil depth, and demonstrably affects the digging behavior of leaf cutting ants.…”
Section: Depthmentioning
confidence: 96%